Pengelolaan Lahan Pertanian Berbasis Kearifan Lokal dengan Memanfaatkan Pekarangan Rumah - Adriana Madya Marampa; Yonana Tandirerung; Helba Rundupadang (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
This Community Service activity was carried out with the theme "Local-Based Food Independence and Innovation" with a focus on the use of home yards to improve food security. The results of observations in Rantekalua' Village showed that yard land management was still less than optimal. Therefore, in this Community Service activity, several Participatory Rural Appraisal methods, Socialization and Extension, Continuous Assistance Methods, Monitoring and Evaluation Methods, Documentation and Dissemination Methods were used. The results of community service are an increase in community skills and community food independence and strengthening family food security. The goal is to disseminate agricultural knowledge derived from local wisdom to the community and encourage behavioral changes oriented towards improving family economy, food independence, and sustainable environmental management. Thus, the purpose of this service is to disseminate local-based agricultural knowledge to the community and encourage positive behavioral changes in order to create food independence and sustainable environmental management.